Heat transfer modelling in an annular disc under heating and cooling processes with stress analysis - Varhadpande, Indrajeet; Murthy, V.R.K.; Lamba, Navneet Kumar (Zielona Góra: Uniwersytet Zielonogórski)
The goal of this effort is to determine the interaction among the heating and cooling processes in order to understand how solids behave when subjected to temperature changes. In this instance, the temperature, displacement, and stress relations are determined analytically and numerically while a thin annular disc is subjected to both the heating and cooling processes. The ability of a material to withstand stress is essential for the design of diverse mechanical structures that aim to enhance performance, durability, characteristics, and strength.
Keywords: memory related derivatives; heating process; cooling process; integral transform; temperature; stress functions